γ-Aminobutyric acidB autoreceptors in substantia nigra and neostriatum of the weaver mutant mouse - Radnikow, Gabriele; Titz, Stefan; Mades, Sandra Hedwig; Bäurle, Jörg; Misgeld, Ulrich (Neuroscience letters, 2001)
The weaver mutation causes cell loss in the center of the substantia nigra, pars compacta. We compared the depression of γ-aminobutyric acid (GABA)A synaptic currents by the GABAB agonist R-baclofen in pars compacta neurons of weaver mice which were largely spared from cell degeneration and of wild-type mice. In weaver neurons the suppression of GABAA synaptic currents by R-baclofen was reduced compared to wild-type neurons. The EC50 of R-baclofen was 6.3 times higher in weaver than in wild-type mice. In the neostriatum, which is not a target of the mutation, such a difference did not exist. We conclude that in the pars compacta the weaver mutation leads to a reduced presynaptic autoinhibition through GABAB receptors which may promote survival of a subset of weaver neurons in the pars compacta.